Effect of boron and zinc varieties and spraying on the vegetative characteristics of three eggplant varieties: Egg plant (Solanum melongenal.L) - Al - Obeidi, Abdul Rasul Hamid Hussein; Mafraji, Othman Khalid Alwan (Journal of agricultural, environmental and veterinary sciences, 2019)
A field experiment was carried out at the research department of the Department of Horticulture and Garden Engineering of the Faculty of Agriculture- Diyala University during the agricultural season 2017 to study the effect of varieties and nutrients on the growth characteristics of three eggplant varieties. On 27-2-2017 seeds were planted The experiment included two factors: the first factor was varieties of the class Black Beauty and Vzlh V1 and the local variety (Abu torso) and called V2 Syrian class Vzlh V3, The second factor was boron (F1) and p2100 (F2) feeder concentrations, with a concentration of 100 ppm for each element and the treatment of F4, which was sprayed with distilled water. The experiment included twelve global treatments, Randomized Complete Block Design (RCBD) and showed the following results: • The local variety (V2) was superior to the rest of the varieties of plant height, leg thickness, number of branches and the average area of the paper, which reached 111.833 cm and 6.46 branches, plants 1, 2.516 cm and 144.0 sheets. 1 and 147.470 cm 2, respectively, while the proportion of chlorophyll V3 significantly above the rest of the varieties at a rate of 38.167 SPAD. • Spraying with boron and zinc (F3) with a concentration of 100ppm per component resulted in a significant increase in plant height, leg thickness, number of branches and chlorophyll ratio, with a ratio of 109.878 cm and 7.05 branches, plants 1, 2.555 cm and 148.775 leaves. Respectively. As for the ratio of the area of one leaf, the treatment of boron F1 failed 100ppm at a level of 131.676 cm2 • The treatment of V2F3 was significantly higher than the rest of the treatments for plant height, number of branches and number of leaves, with 122.3 cm, 7.40 branches, plants 1 and 165.60 leaves, respectively, while V3F3 significantly exceeded the rest of the treatments And chlorophyll ratio of 2.73 cm and 44.16 respectively.